FOLFIRINOX for Advanced Pancreatic Cancer Patients After Nab-Paclitaxel Plus Gemcitabine Failure. Issue 4 (April 2020) - Matsumoto, Toshihiko; Kurioka, Yusuke; Okazaki, Ukyo; Matsuo, Yu; Kimura, Shogo; Miura, Kou; Tsuduki, Takao; Takagi, Shinjiro; Takatani, Masahiro; Morishita, Hirofumi
Abstract : Objectives: There is no standard chemotherapy for advanced pancreatic cancer (APC) after gemcitabine plus nab-paclitaxel (GP) failure. The aim of this study was to evaluate the efficacy and safety of FOLFIRINOX (5-Fluorouracil, leucovorin, irinotecan, and oxaliplatin) (5-Fluorouracil, leucovorin, irinotecan, and oxaliplatin) (FFX) and modified FFX (mFFX) for APC patients after GP failure. Methods: We retrospectively evaluated the efficacy and safety of FFX in APC patients who were refractory or intolerant of GP. Results: Between July 2014 and October 2018, 23 patients received FFX after failure of GP. The overall response rate (RR) was 23%, and the disease control rate (DCR) was 68%. The median progression-free survival (PFS) was 5.3 months (95% confidence interval, 2.5–8.9), and the median overall survival (OS) was 12.1 months (95% confidence interval, 4.0–14.2). Twelve patients received FFX, and 11 patients received mFFX. In the FFX group, the RR was 9%, the DCR was 73%, the PFS was 5.3 months, and the OS was 6.9 months. In the mFFX group, the RR was 23%, the DCR was 64%, the PFS was 4.3 months, and the OS was 12.8 months. There was no significant difference between the groups. Conclusions: FOLFIRINOX has potential activity for patients with APC in whom GP failed.